2013
DOI: 10.1371/journal.pone.0062815
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Colonoscopy Bowel Preparation on Intestinal Microbiota

Abstract: The gut microbiota is important in maintaining human health, but numerous factors have the potential to alter its composition. Our aim was to examine the impact of a standard bowel preparation on the intestinal microbiota using two different techniques. Fifteen subjects undergoing colonoscopy consumed a bowel preparation comprised of 10 mg bisacodyl and 2 L polyethylene glycol. The microbiota of stool samples, collected one month before, one week before (pre-colonoscopy), and one week, one month, and three to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 32 publications
(42 reference statements)
5
71
1
Order By: Relevance
“…Our group has previously demonstrated that bowel preparation and colonoscopy does not change the microbiota in most subjects, 30 but noted that three patients suffering from ulcerative colitis did not have restoration of their pre-colonoscopy microbiome. Therapeutic manipulation of the microbiome, for example with faecal microbial transplantation, has had mixed results in IBD cohorts compared to those with recurrent Clostridium difficile colitis, 31 , 32 also raising the possibility that there is instability of the microbiome in IBD patients compared to previously healthy subjects.…”
Section: Discussionmentioning
confidence: 91%
“…Our group has previously demonstrated that bowel preparation and colonoscopy does not change the microbiota in most subjects, 30 but noted that three patients suffering from ulcerative colitis did not have restoration of their pre-colonoscopy microbiome. Therapeutic manipulation of the microbiome, for example with faecal microbial transplantation, has had mixed results in IBD cohorts compared to those with recurrent Clostridium difficile colitis, 31 , 32 also raising the possibility that there is instability of the microbiome in IBD patients compared to previously healthy subjects.…”
Section: Discussionmentioning
confidence: 91%
“…Harrel et al 47 split the subjects into three groups to compare the impact on the microbiota of MBP or a liquid diet for 24 hours with no bowel preparation (box 2). O'Brien et al 48 analysed the microbiota in stool samples collected 1 month and 1 week before and 1 week, 1 month and 3 months after MBP using denaturing gradient gel electrophoresis (DGGE) and high-throughput sequencing (HTS) methods. Jalanka et al 49 was the first (and at present, the only) study to examine the effect of two cleansing regimens on faecal microbiota composition.…”
Section: The Impact Of Preoperative Mechanical Bowel Preparation Withmentioning
confidence: 99%
“…significantly affect the gut microbiota in the long term (24,25). The short term effects of bowel preparation may be due to the majority of the bacteria being washed out in a nondiscriminatory manner, which could reduce low-abundance taxonomic groups to levels below detection; on average, bowel preparation with polyethylene glycol can reduce bacterial load by 34.7-fold (25).…”
Section: Studies By O"brien Et Al and Jalanka Et Al Confirm That Comentioning
confidence: 99%